1995
DOI: 10.1126/science.267.5196.362
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Linear Acetylenic Carbon: The " sp " Carbon Allotrope

Abstract: A carbon allotrope based on "sp" hybridization containing alternating triple and single bonds (an acetylenic or linear carbon allotrope) has been prepared. Studies of small (8 to 28 carbon atoms) acetylenic carbon model compounds show that such species are quite stable (130 degrees to 140 degrees C) provided that nonreactive terminal groups or end caps (such as tert-butyl or trifluoromethyl) are present to stabilize these molecules against further reactions. In the presence of end capping groups, laser-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
182
0
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(194 citation statements)
references
References 20 publications
(1 reference statement)
5
182
0
7
Order By: Relevance
“…It is suggested that terminal alkyne building blocks can be in general covalently linked on suitable noble metal surfaces to create novel molecular compounds, low-dimensional superstructures or coherently reticulated polymeric layers. This provides a new synthesis route towards conjugated molecular nanosystems and networks, providing potential for the fabrication of regular 1D scaffolds, such as carbyne 40,41 , 2D polymers, such as graphyne or graphdiyne 6,42 , and similar hydrocarbon membranes. We furthermore envision the use of nanostructured interfaces and noble metal nanoparticles as catalytic materials and reaction templates under vacuum or other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that terminal alkyne building blocks can be in general covalently linked on suitable noble metal surfaces to create novel molecular compounds, low-dimensional superstructures or coherently reticulated polymeric layers. This provides a new synthesis route towards conjugated molecular nanosystems and networks, providing potential for the fabrication of regular 1D scaffolds, such as carbyne 40,41 , 2D polymers, such as graphyne or graphdiyne 6,42 , and similar hydrocarbon membranes. We furthermore envision the use of nanostructured interfaces and noble metal nanoparticles as catalytic materials and reaction templates under vacuum or other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] However, little has been experimentally demonstrated mainly due to the lack of a reliable and effective fabrication method. [20][21][22][23][24] The present work suggests that such 1D carbon chains can be formed via self-assembly on Cu(111) substrates.…”
mentioning
confidence: 94%
“…We have therefore studied the effect of multideterminant (MD) Slater-Jastrow trial wave functions for excited, cationic, and anionic states of oligoynes with 4,6,8,10, and 24 carbon atoms as well as a supercell of polyyne composed of 8 primitive cells. The Slater determinants in the MD wave functions contained all the orbital occupancies that are degenerate at the single-particle level.…”
Section: B Qmc Calculationsmentioning
confidence: 99%
“…The observed presence of carbon chains in interstellar space and circumstellar shells 1,2 has inspired considerable effort to synthesise polyyne in the laboratory, leading among other things to the discovery of fullerenes 3 . Recent experiments have shown that it is possible to produce a long linear chain of more than 200 carbon atoms inside a protector such as a double-walled carbon nanotube (DWCNT) 4 and also to synthesise stable oligoynes (short polyyne molecules) with up to 44 carbon atoms 5 and a variety of terminal groups [6][7][8][9][10][11][12] . Polyyne is of particular interest as the ideal interconnect in single-molecule nanoelectronic circuitry, including spintronic devices [13][14][15][16] , and has potential applications in nanomechanical devices [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%